2016
DOI: 10.1158/1535-7163.mct-16-0297
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pharmacodynamic Transcript Biomarkers in Response toFGFRInhibition by AZD4547

Abstract: The challenge of developing effective pharmacodynamic biomarkers for preclinical and clinical testing of FGFR signaling inhibition is significant. Assays that rely on the measurement of phospho-protein epitopes can be limited by the availability of effective antibody detection reagents. Transcript profiling enables accurate quantification of many biomarkers and provides a broader representation of pathway modulation. To identify dynamic transcript biomarkers of FGFR signaling inhibition by AZD4547, a potent in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
1
23
1
Order By: Relevance
“…Contrary to our findings, a recent study found that FRS2 knockdown promotes tumor progression in two NB cell lines . However, FRS2 is amplified in many cancer types so FRS2 presents typical oncogenic features . Furthermore, the focal amplification of 12q15 region in many cancers, as in primary NB tissues, is correlated with increased mRNA expression of FRS2 , suggesting a functional relevance of the copy number gain.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings, a recent study found that FRS2 knockdown promotes tumor progression in two NB cell lines . However, FRS2 is amplified in many cancer types so FRS2 presents typical oncogenic features . Furthermore, the focal amplification of 12q15 region in many cancers, as in primary NB tissues, is correlated with increased mRNA expression of FRS2 , suggesting a functional relevance of the copy number gain.…”
Section: Discussioncontrasting
confidence: 99%
“…The FRS2 gene is located close to MDM2 and CDK4 within the 12q13‐15 segment. FRS2 is a key adaptor protein in the fibroblast growth factor receptor (FGFR) pathway, binding to FGFR and subsequently activating downstream signaling cascades . FRS2 is involved in cell differentiation and proliferation, inducing downstream activation of the RAS‐MAPK pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further assess FGF pathway activity, we measured a panel of transcripts shown to reflect the dynamic output of FGF receptor (FGFR) signaling (Delpuech et al, 2016). Several transcripts comprising this FGFR signature were increased more than 10-fold in LNCaP APIPC cells including DUSP6 , ETV4 , and EGR1 , and LNCaP APIPC cells showed significant FGFR and MAPK pathway enrichment scores (Figure 3K).…”
Section: Resultsmentioning
confidence: 99%
“…Since NSCLC cell lines expressed multiple FGFs and FGFRs, we used phosphorylation of the FGFR docking protein fibroblast growth factor receptor substrate 2 (FRS2) [24] as a readout for signaling from the FGFR pathway in the presence of AZD4547 and fulvestrant (Figure 5). Cells were treated with DMSO vehicle, AZD4547, fulvestrant or the combination and cell lysates were probed for phospho-FRS2 (pFRS2).…”
Section: Resultsmentioning
confidence: 99%